SYNTHESIS, ANTIAGGREGATION AND ANTITROMBOTIC ACTIVITIES OF NEW DERIVATIVES OF HYDROXYBENZOIC ACIDS WITH TAURIC FRAGMENT - A. K. Brel; N. V. Atapina; Yu. N. Budaeva; S. V. Lisina; S. S. Tsaruk; D. V. Kurkin; I. N. Tyurenkov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
A high prevalence of thrombotic disorders, insufficient effectiveness or safety of antithrombotic therapy is an urgent problem of modern healthcare. The main means of preventing thrombosis is acetylsalicylic acid. Despite its long history, aspirin attracts researchers in the fields of medicinal chemistry, biology, and medicine. The development of new antiplatelet agents, including chemical modification of the acetylsalicylic acid molecule, remains relevant. Modification of the acetylsalicylic acid molecule using amino acids and obtaining their salt forms makes it possible to maintain antiplatelet or antithrombotic properties, as well as to impart additional pharmacodynamic effects. In modern science, a lot of attention is paid to the sulfur-containing amino acid taurine. An analysis of modern scientific literature revealed the protective effect of taurine in diabetes mellitus and cardiovascular diseases, liver dysfunction, gastrointestinal tract, and kidney diseases.The aim of the article is to study synthesis of new compounds, determination of their physical characteristics and assessment of their antiplatelet and antithrombotic activities in vitro and in vivo.Materials and methods. To confirm the structure of the synthesized new derivatives of hydroxybenzoic acids with a taurine fragment by the acelation method, thin layer chromatography and NMR spectra were used. In vitro studies were carried out on the model of ADP-induced platelet aggregation according to the Born G. methods modified by V.A. Gabbasov. In vivo, the studies were carried out on the model of arterial thrombosis induced by the application of iron chloride in the following groups of animals: intact, with experimental diabetes mellitus and three-year-olds; the rate of bleeding from the tail vein was also evaluated.Results. New compounds - derivatives of ortho-, meta- and para-hydroxybenzoic acids with a taurine residue - were synthesized. A procedure for the preparation of N-hydroxybenzoyl taurine compounds and their salt forms have been described; their spectral characteristics and melting points have been determined. The synthesized compounds are superior to acetylsalicylic acid in solubility and are not inferior to it in antiplatelet and antithrombotic activities. The results of the in vitro antiplatelet activity assessment in a wide concentration range from 10-4M to 10-8M, are presented. It has been revealed that the dipotassium salt of N-(2-hydroxybenzoyl)taurine exhibits a less antiplatelet activity than the dipotassium salt of N-(3-hydroxybenzoyl)taurine. The most pronounced antiplatelet activity is exhibited by the compound N-(4-hydroxybenzoyl)taurine. In in vivo experiments on the model of arterial thrombosis in 3-year-olds or animals with experimental diabetes mellitus, carotid artery thrombosis occurred faster than in young or intact animals. A single preliminary oral administration of the test compounds prolonged the time of the thrombus formation, which makes it possible to conclude that they have an antithrombotic effect. In this study, the dipotassium salt of N-(3-hydroxybenzoyl)taurine exhibits a more pronounced activity than that of acetylsalicylic acid.Conclusion. Against the background of the modeled pathologies, the studied drugs showed the expected antithrombotic activity, in terms of the severity not inferior to that found in acetylsalicylic acid.